The effect of E-learning in communicating knowledge for Jordanian public school students (A prospective study of Halima Al-Sa`dia Secondary School for Girls) - Ghanem, Amneh Khalil Abdallah (Journal of Educational and Psychological Sciences, 2022)
The study aimed at identifying the impact of E-learning in communicating knowledge to students of Jordanian public schools. To achieve this goal, the descriptive analytical approach was used, the study questionnaire was applied to 36 female teachers at Halima Al Saadia Secondary School for Girls during the first semester of the academic year 2021/2022. The study revealed that the axis of readiness of Halima Al-Sa`dia Secondary School for Girls for E-learning was high, and the axis of teachers evaluation of E-learning was low, as for the level of students’ interaction at Halima Al Saadia Secondary School for Girls with E-learning was average. In terms of statistically significant differences at the significance level (0.05) in the level of E-learning effectiveness in Halima Al-Sa`dia Secondary School for Girls, on the dimensions (Readiness of Halima Al-Sa`dia Secondary School for Girls for E-learning, the evaluation of the teachers of Halima Al-Sa`dia Secondary School for Girls for E-learning, and the level of students’ interaction at Halima Al-Saadiya Secondary School for Girls with E-learning), it appears that there were no statistically significant differences at the significance level (0.05) either to the variable of the age group, nor to the variable years of teaching experience. In light of these results, the study proposed a set of reccomedations including holding more various training courses for students and teachers for practical training on the E-learning system, to view the latest programs and developments in the field of e-learning, and to encourage teachers to contact students through web pages, e-mails and other electronic communications.